Perspectives of undergraduate piano students on the use of the MIROR-Impro software for developing their improvisation skills (Orfeu, 2019)
Recent research studies have provided evidence on the benefits of using digital technology to improve specific aspects of instrumental and vocal learning in the context of individual lessons. The application of digital technology can generate types of feedback additional to that provided by the teacher which are commonly found in individual classes. Additional feedback types are real-time and post-hoc visual feedback combined with auditory feedback may increase student awareness of their learning process. Improvisation can be a challenge for undergraduate students in Bachelors in Piano Performance who have the piano as the principal instrument in which the lesson focus is on developing piano technique and interpretative skills to perform solo repertoire different periods. The objective of this research is to investigate the development of improvisation with regular undergraduates of the Bachelor’s Degree in Piano of a Brazilian higher education institution, using reflexive interaction with the MIROR-Impro software, one of the components of the MIROR plataform (Musical Interaction Relying On Reflexion). Two undergraduate piano major students had two sessions recorded on video for observation data whilst they explored the use of MIROR-Impro software, and were interviewed for two times; this approach was conducted to understand students’ perspectives on the use of this technology system. Piano undergraduates’ reports assist on the understanding of the application of the use of the MIROR-Impro software, its benefits and limitations regarding, for developing improvisations in keyboard instruments.
Keywords: Music Education and Digital Technologies; Feedback; Improvisation; Piano Pedagogy; Musical Interaction Relying on Reflexion